2017
DOI: 10.22271/ortho.2017.v3.i1f.56
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mesenchymal stem cells in healing of meniscus tear

Abstract: The aesthetic appearance of the thumb hasn't been analysed to a similar extent as thumb function which would aid during reconstructive surgeries of the thumb and first web space and analyse its outcome. The purpose of this study is to determine the relative length, girth, nail width of thumb with respect to the index finger and intermetacarpal distance. Measurement of the 1 st web space arc radius has been done to tackle the problem of webbing which is not addressed by IMD and palmar abduction angles. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…90 Another recent randomized, double-blinded trial performed intra-articular injection of mesenchymal stem cells in 2 groups of 15 patients with clinical and imaging diagnosed meniscus tears. 91 Significant clinical improvement in pain and resolution of MRI signal change was noted in the group that received the stemcell injection in comparison to the placebo control group.…”
Section: Stem Cellsmentioning
confidence: 93%
See 1 more Smart Citation
“…90 Another recent randomized, double-blinded trial performed intra-articular injection of mesenchymal stem cells in 2 groups of 15 patients with clinical and imaging diagnosed meniscus tears. 91 Significant clinical improvement in pain and resolution of MRI signal change was noted in the group that received the stemcell injection in comparison to the placebo control group.…”
Section: Stem Cellsmentioning
confidence: 93%
“…A randomized, double-blinded trial demonstrated meniscus regeneration on the basis of increased size (24%) on MRI and significant reductions in pain in patients treated with mesenchymal stem cell injections that had a prior medial meniscectomy 90. Another recent randomized, double-blinded trial performed intra-articular injection of mesenchymal stem cells in 2 groups of 15 patients with clinical and imaging diagnosed meniscus tears 91. Significant clinical improvement in pain and resolution of MRI signal change was noted in the group that received the stem-cell injection in comparison to the placebo control group.…”
Section: Stem Cellsmentioning
confidence: 99%